Macrophage polarization differs between apical granulomas, radicular cysts, and dentigerous cysts - Weber, Manuel; Schlittenbauer, Tilo; Möbius, Patrick; Büttner-Herold, Maike; Ries, Jutta; Preidl, Raimund; Geppert, Carol-Immanuel; Neukam, Friedrich Wilhelm; Wehrhan, Falk (Clinical Oral Investigations, 2017)
Apical periodontitis can appear clinically as apical granulomas or radicular cysts. There is evidence that immunologic factors are involved in the pathogenesis of both pathologies. In contrast to radicular cysts, the dentigerous cysts have a developmental origin. Macrophage polarization (M1 vs M2) is a main regulator of tissue homeostasis and differentiation. There are no studies comparing macrophage polarization in apical granulomas, radicular cysts, and dentigerous cysts.Forty-one apical granulomas, 23 radicular cysts, and 23 dentigerous cysts were analyzed in this study. A tissue microarray (TMA) of the 87 consecutive specimens was created, and CD68-, CD11c-, CD163-, and MRC1-positive macrophages were detected by immunohistochemical methods. TMAs were digitized, and the expression of macrophage markers was quantitatively assessed.Radicular cysts are characterized by M1 polarization of macrophages while apical granulomas show a significantly higher degree of M2 polarization. Dentigerous cysts have a significantly lower M1 polarization than both analyzed periapical lesions (apical granulomas and radicular cysts) and accordingly, a significantly higher M2 polarization than radicular cysts. Macrophage cell density in dentigerous cysts is significantly lower than in the periapical lesions.The development of apical periodontitis towards apical granulomas or radicular cysts might be directed by macrophage polarization. Radicular cyst formation is associated with an increased M1 polarization of infiltrating macrophages. In contrast to radicular cysts, dentigerous cysts are characterized by a low macrophage infiltration and a high degree of M2 polarization, possibly reflecting their developmental rather than inflammatory origin.As M1 polarization of macrophages is triggered by bacterial antigens, these results underline the need for sufficient bacterial clearance during endodontic treatment to prevent a possible M1 macrophage-derived stimulus for radicular cyst formation.
EVALuna2:6886